Uji Anti Bakteri dan Identifikasi Senyawa Antibiotika yang Dihasilkan Streptomyces Sp - I.A. Rivai bakti; Budi Untari; Frida Oesman; Emilia Fitriani (Jurnal Penelitian Sains, 1999)
It has been isolated identified anti bacterium of antibiotic compunds produced by streptomyces sp. The isolation of sterptomyces sp was done from three kinds of soil on Soak area Km . 6, Palembang Municipallity using Plating Technic Spread Method produced 4 streptomyces isolate,. The test of the blocked capacity againts the whole isolates (4 isolates) with the bactery terstor showed that TL.J2 isolate from corn plant land has biggest activities. The isolates of antibiotics produced using fermentation method for TL.J2 isolates by using solvent extraction method and continued with HPLC produced 4 pure compunds. The test of the blocked capacity againts the 4 pure compunds, just STP1 which still antibacteria activities. Furthermore, the identification of STP1 using IR Spectrophotometer and UV showed that the results can be clasified into Alifaitic antibiotic consisting of unsaturated ketod alifatic function with the primer amine and hydroxy as a substiutent.